Photoluminescence: MoS2 and Perylene Derivative Based Type‐II Heterostructure: Bandgap Engineering and Giant Photoluminescence Enhancement (Adv. Mater. Interfaces 2/2020). Issue 3 (7th February 2020) - Obaidulla, Sk Md; Habib, Mohammad Rezwan; Khan, Yahya; Kong, Yuhan; Liang, Tao; Xu, Mingsheng
Abstract : Combination of perylene derivatives and MoS2 exhibit contrasting photoluminescence (PL) behavior. The intense PL emission exhibits in PTCDA/MoS2 while quenching in PTCDI‐Ph/MoS2 . The observed giant PL enhancement of PTCDA/MoS2 is due to the reduced bandgap, large exciton/trion ratio, and ordered morphology of PTCDA. The results can stimulate optoelectronic based novel applications. More details can be found in article number 1901197 by Sk Md Obaidulla, Mingsheng Xu, and co‐workers.